Reaktualisasi Konsep Ghadd Al-Basar dalam Qs. An-Nur Ayat 30–31 pada Fenomena Lurking di Ruang Siber: Analisis Tafsir Al-Misbah - Shelma; Ali Darta (Kartika: Jurnal Studi Keislaman, 2026)
The rise of social media has given rise to lurking, the passive observation of others’ digital activities without direct interaction. This behavior bears functional similarities to the concept of gaze (al-nazar) addressed in QS. An-Nur 30–31 through the injunction of ghadd al-basar (lowering the gaze). This study aims to analyze M. Quraish Shihab's interpretation in Tafsir Al-Misbah of these verses and to formulate its reactualization as an ethical framework for addressing the phenomenon of lurking in cyberspace. This is a qualitative study employing a thematic (maudu’i) exegetical approach and library research, using Tafsir Al-Misbah as the primary data source and literature on digital ethics and online behavior as secondary data. The findings indicate that Quraish Shihab interprets ghadd al-basar not merely as a prohibition against physically viewing another's 'awrah, but as a principle of gaze-control rooted in self-awareness and the preservation of dignity, both one's own and that of others. This principle is relevant for reactualization in the context of cyberspace lurking, since contemporary "gazing" is no longer limited to the physical sense of sight but extends to the practice of accessing, observing, and consuming others' digital traces. The reactualization of ghadd al-basar values can serve as a foundation for social media ethics that emphasizes boundary awareness, respect for privacy, and self-restraint in cyberspace interaction.